Explaining Regional Inflation Programmes in Indonesia: Does Inflation Rate Converge? - Rudi Purwono, Dr (Netherlands Springer, 2020)
This paper investigates the inflation convergence of 82 Indonesian cities and discusses the remarkable regional inflation programmes in Indonesia. By employing a dynamic panel regression, the paper shows that Indonesia experienced an inflation convergence from 2013 to 2018. An intriguing finding is that the cities in Java-Bali, the largest density area, experienced a slower speed of convergence than that in cities outside the Java-Bali. This paper alleges that the development of logistic transportation and the formulation of an inflation control programme, such as the Tim Pengendalian Inflasi Daerah (TPID) or Regional Inflation Controlling Team (RICT) that has just been stationed and has commenced their duties in East Indonesia, might play an essential role in the convergence. Moreover, the coordination between the central and regional governments, represented by TPID/RICT, in implementing the effective policy (i.e. prioritising development outside Java-Bali and fostering inter-region cooperation in the commodity supply chain) is effective in stabilising and reducing the inflation rate.